2015
DOI: 10.1111/jch.12760
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Total Isoflavone Intake Is Associated With Lower Systolic Blood Pressure: The Coronary Artery Risk Development in Young Adults (CARDIA) Study

Abstract: The effect of dietary isoflavone intake on systolic blood pressure (SBP) has not been studied in a large community-based cohort inclusive of African Americans. We analyzed data from the year 20 exam of the Coronary Artery Risk Development in Young Adults (CARDIA) study, including medical history, physical exam and dietary intake surveys for 3,142 participants. Multivariable linear regression models controlled for age, sex, BMI, smoking, physical activity, and intakes of alcohol and total energy. Effect modific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…Proposed cardioprotective mechanisms for flavonoids include antioxidant and anti-inflammatory action, modulation of lipid metabolism and platelet function, and attenuation of hypertension (2). Consistent with proposed biological mechanisms, results from epidemiologic studies suggest a protective effect for flavonoids against cardiovascular disease mortality (1, 3, 4), incident coronary heart disease (5,6), and incident stroke (7), as well as other indicators of cardiovascular risk, such as arterial stiffness, incident hypertension, and type 2 diabetes (8)(9)(10)(11). Although dietary flavonoid research has progressed over the past decade, existing literature is limited by incomplete dietary flavonoid information and lack of geographic and racial/ethnic diversity of studied populations, especially in the context of incident stroke.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Proposed cardioprotective mechanisms for flavonoids include antioxidant and anti-inflammatory action, modulation of lipid metabolism and platelet function, and attenuation of hypertension (2). Consistent with proposed biological mechanisms, results from epidemiologic studies suggest a protective effect for flavonoids against cardiovascular disease mortality (1, 3, 4), incident coronary heart disease (5,6), and incident stroke (7), as well as other indicators of cardiovascular risk, such as arterial stiffness, incident hypertension, and type 2 diabetes (8)(9)(10)(11). Although dietary flavonoid research has progressed over the past decade, existing literature is limited by incomplete dietary flavonoid information and lack of geographic and racial/ethnic diversity of studied populations, especially in the context of incident stroke.…”
Section: Introductionmentioning
confidence: 79%
“…Regional disparities in stroke may be related to lower flavanone intake in residents of the Stroke Belt and Stroke Buckle. One published study addressed modification of the association between isoflavone intake and blood pressure by race, which suggests stimulation of endothelial nitric oxide synthase in the setting of relative nitric oxide deficiency as a potential mechanism to explain a stronger beneficial association between dietary isoflavone and blood pressure in black participants than in white participants (11). Other flavonoid subclasses have been implicated in nitric oxide modulation (40), but to our knowledge, no other studies in humans have been published that allow comparison of results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary isoflavones, obtained through soy-based foods such as tofu and tempeh, independently associate with lower systolic BP and may exert their effects through endothelium-dependent vasodilation. 47 Soy protein is rich in arginine, an essential component of the nitric oxide pathway, which may help promote vasodilation. 48 Moreover, vegetables are rich in potassium, a micronutrient that has also been shown to reduce BP in randomized controlled trials.…”
Section: Discussionmentioning
confidence: 99%
“…Isoflavones have been found to be beneficial in a wide range of diseases and have beneficial effects on some physiological risk factors for chronic kidney disease, such as dyslipidemia [ 30 ], hypertension [ 31 ], DM [ 32 ], and obesity [ 33 ]. In vitro studies [ 34 , 35 , 36 ] have shown that isoflavones downregulate several proinflammatory mediators like tumor necrosis factor-alpha (TNF-α), interleukin (IL)-6, IL-8, IL-1β, prostaglandin E2 (PGE2), monocyte chemoattractant protein-1, and intercellular adhesion molecule-1, or they upregulate anti-inflammatory cytokines like IL-10 [ 37 ].…”
Section: Introductionmentioning
confidence: 99%